To use the additive inverse to find \(-492.89 - (-871.78)\), we can rewrite the expression:
\[ -492.89 - (-871.78) = -492.89 + 871.78 \]
Next, we can perform the addition:
\[ -492.89 + 871.78 \]
To do this, we can convert \(-492.89\) to a positive number and then perform the subtraction:
\[ 871.78 - 492.89 \]
Now, let's calculate that step:
- Align the numbers by decimal:
871.78
- 492.89
-
Subtract from right to left:
-
In the hundredths place: 8 - 9 requires borrowing:
- 7 becomes 6, and we take 1 from the tenths (making it 1)
- So, 18 - 9 = 9
-
In the tenths place: 1 (after borrowing) - 8 needs borrowing:
- 6 becomes 5, and we take 1 from the ones (making it 7)
- So, 11 - 8 = 3
-
In the ones place: 7 - 2 = 5
-
In the tens place: 5 - 9 requires borrowing:
- 8 becomes 7, and we take 1 from the hundreds (making it 7)
- So, 15 - 9 = 6
-
In the hundreds place: 7 - 4 = 3
-
Putting it all together, we have:
871.78
- 492.89
---------
378.89
So, the final result is:
\[ -492.89 - (-871.78) = 378.89 \]
Therefore, \(-492.89 - (-871.78) = 378.89\).